2009
DOI: 10.1021/ja8094526
|View full text |Cite
|
Sign up to set email alerts
|

Charge and Temperature Dependence of Biomolecule Conformations: K+Tryptamine(H2O)n=0−1Arm=0−1 Cluster Ions

Abstract: The impact of temperature and charge on the conformation of tryptamine (Tryp) is examined in the gas phase by infrared laser-vibrational predissociation spectroscopy in the 2800-3800 cm(-1) region. Previous studies of neutral Tryp(H(2)O)(n) clusters showed preferential stabilization of specific tryptamine conformers through hydrogen bonding. When complexed with the biologically significant potassium ion, the only conformers found to form under these experimental conditions are built on hitherto unobserved neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 16 publications
5
49
0
1
Order By: Relevance
“…33 Results for hydrated, potassiated tryptamine indicate that temperature can have a strong influence on ion hydration, and isomers calculated to be ∼20 kJ/mol higher in energy than the lowest-energy structure were found to contribute substantially to the ∼50-150 K IRPD spectrum of this ion, indicating kinetic trapping of high-energy structures or substantial uncertainties in calculated energies. 76 Pioneering IRPD spectroscopy studies by Rizzo and coworkers of ValH + (H 2 O) 1-4 are consistent with addition of the first three water molecules to the protonated N-terminus before the uncharged C-terminus is hydrated based on the presence of a spectral band associated with a bare carboxylic acid group. 27 However, the absence of bands attributable to a hydrated C-terminus in these spectra does not eliminate the possibility that some C-terminally hydrated isomers are present in the ion population, and computational results at the B3LYP/6-31++G** level of theory favor C-terminal hydration upon addition of the second water molecule.…”
Section: Introductionmentioning
confidence: 67%
“…33 Results for hydrated, potassiated tryptamine indicate that temperature can have a strong influence on ion hydration, and isomers calculated to be ∼20 kJ/mol higher in energy than the lowest-energy structure were found to contribute substantially to the ∼50-150 K IRPD spectrum of this ion, indicating kinetic trapping of high-energy structures or substantial uncertainties in calculated energies. 76 Pioneering IRPD spectroscopy studies by Rizzo and coworkers of ValH + (H 2 O) 1-4 are consistent with addition of the first three water molecules to the protonated N-terminus before the uncharged C-terminus is hydrated based on the presence of a spectral band associated with a bare carboxylic acid group. 27 However, the absence of bands attributable to a hydrated C-terminus in these spectra does not eliminate the possibility that some C-terminally hydrated isomers are present in the ion population, and computational results at the B3LYP/6-31++G** level of theory favor C-terminal hydration upon addition of the second water molecule.…”
Section: Introductionmentioning
confidence: 67%
“…Some studies have employed a single scaling factor for all vibrations (e.g., 0.952 by Rizzo and coworkers [45], and 0.96 by Mons and coworkers [46]), depending on the level of theory that was chosen. Others have employed variable scaling factors for NH and OH vibrations (e.g., 0.956 for NH and 0.976 for OH by Snoek and coworkers [47], and 0.959 for NH and 0.976 for OH by Lisy and coworkers [48]). The use of different scaling factors for NH and OH vibrations is often warranted, due to differences in the anharmonicities for OH and NH modes, which harmonic calculations do not account for.…”
Section: General Considerations For Diagnostic Nh and Oh Band Positionsmentioning
confidence: 99%
“…One or a limited number of conformers are thus populated. However, numerous studies have shown that the formation of complexes in a supersonic expansion is not always under thermodynamic control [39][40][41][42][43] Higher energy conformers can be observed in the supersonic expansion; thermodynamically stable forms might be absent if the barrier to their formation is too high (kinetic control) [44][45][46].…”
Section: A Zehnackermentioning
confidence: 99%
“…Besides the fact that K + stabilises higher energy conformers of tryptamine, a higher energy conformer of the complex trapped by the argon evaporative cooling process has been observed [43].…”
mentioning
confidence: 97%
See 1 more Smart Citation